Gaya Kepemimpinan Transformasional dan Kesejahteraan Psikologis Karyawan di PT Primayudha Mandirijaya Kabupaten Boyolali Jawa Tengah - Abadi, Andhika Wijaya; Wijono, Sutarto (Jurnal Ilmiah Psyche, 2023)
Abstract : The purpose of the study was to determine whether there is a relationship between transformational leadership style and psychological well-being of permanent employees of the production department who work at PT. Primayudha Mandirijaya. This research uses quantitative methods and descriptive statistical analysis, with pearson product moment techniques. Determinant of non-probability sampling technique with a total sample of 83 permanent employees of the production department at PT. Primayudha Mandirijaya. The measuring instruments used in this study were the mulmultifactor leadership scale developed by Bass and Avolio (1995) and the psyho logical well-being scales developed by Ryff (1989). The results of the analysis were obtained with a number of 0,435 and a significance value of 0.000 (< p 0.05), meaning that there is a positive and significant relationship between transformational leadership style and psychological well-being in permanent employees of the production department at PT. Primayudha Mandirijaya in Ampel, Boyolali District. This means that the higher the transformational leadership style, the higher the psychological well-being, conversely, the lower the transformational leadership style, the lower the psychological well-being. Keywords: Transformational leadership, psychological well-being, production department Abstrak : Tujuan dari penelitian adalah untuk mengetahui apakah ada hubungan antara gaya kepemimpinan transformasional dan kesejahteraan psikologis karyawan para karyawan tetap bagian produksi yang bekerja di PT. Primayudha Mandirijaya. Penelitian ini menggunakan metode kuantitatif dan analisa statistik deskriptif, dengan tehnik pearson product moment. Penentu teknik pengambilan sampel non probability sampling dengan jumlah sampel sebanyak 83 karyawan tetap bagian produksi di PT. Primayudha Mandirijaya. Alat ukur yang digunakan dalam penelitian ini adalah mulmultifactor leadership scale yang dikembangkan oleh Bass dan Avolio (1995) dan psyhological well-being scales dikembangkan oleh Ryff (1989). Hasil analisa diperoleh dengan angka 0,435 dan nilai signifikansi 0,000 (< p 0,05) artinya terdapat hubungan positif dan signifikan antara gaya kepemimpinan transformasional dan kesejahteraan psikologis pada karyawan tetap bagian produksi di PT. Primayudha Mandirijaya di Ampel Kab. Boyolali. Artinya semakin tinggi gaya kepemimpinan transformasional maka semakin tinggi pula kesejahteraan psikologis, sebaliknya semakin rendah gaya kepemimpinan transformasional maka semakin rendah juga kesejahteraan psikologis. Kata Kunci : Kepemimpinan transformasional, kesejahteraan psikologis, departemen produksi